Separate and combined associations of obesity and metabolic health with coronary heart disease: a pan-European case-cohort analysis (2018)
ABSTRACT: Aims—The hypothesis of “metabolically healthy obesity” implies that, in the absence of metabolic dysfunction, individuals with excess adiposity are not at greater cardiovascular risk. We tested this hypothesis in a large pan-European prospective study. Methods and results—We conducted a case-cohort analysis in the 520,000-person European Prospective Investigation into Cancer and Nutrition study (“EPIC-CVD”). During median followup of 12.2 years, we recorded 7,637 incident coronary heart disease (CHD) cases. Using cut-offs recommended by guidelines, we defined obesity and overweight using BMI, and metabolic dysfunction (“unhealthy”) as ≥3 of elevated blood pressure, hypertriglyceridemia, low HDL cholesterol, hyperglycemia, elevated waist circumference. We calculated hazard ratios (HRs) and 95% confidence intervals (95% CI) within each country using Prentice-weighted Cox proportional hazard regressions, accounting for age, sex, centre, education, smoking, diet and physical activity. Compared to metabolically healthy normal weight people (reference), HRs were 2.15 (95%CI: 1.79; 2.57) for unhealthy normal weight, 2.33 (1.97; 2.76) for unhealthy overweight, and 2.54 (2.21; 2.92) for unhealthy obese people. Compared to the reference group, HRs were 1.26 (1.17; 1.36) and 1.28 (1.05; 1.56) for metabolically healthy overweight and obese people, respectively. These results were robust to various sensitivity analyses. Conclusion—Irrespective of BMI, metabolically unhealthy individuals had higher CHD risk than their healthy counterparts. Conversely, irrespective of metabolic health, overweight and obese people had higher CHD risk than lean people. These findings challenge the concept of “metabolically healthy obesity”, encouraging population-wide strategies to tackle obesity.